One health insights into pastoralists’ perceptions on zoonotic diseases in Ethiopia: perspectives from South Omo Zone of SNNP Region - Alemu, S.T.; Ero, D.; Mor, Siobhan M. (Springer, 2023)
Zoonotic diseases negatively impact pastoral communities in Ethiopia. In addition to impacts on human health, the interaction between people, livestock and environment which is so fundamental to the pastoralist way of life, means zoonoses pose additional challenges to social bonds and protection networks. These challenges are compounded by adverse impacts from climate change, poor health care services, market problems and cultural practices that increase pastoralists’ vulnerability to zoonotic diseases. This research adopted a grounded theory approach and attempted to capture the perception of Hamer and Dassenetch pastoralists on zoonotic diseases and rangeland health through focus group discussions and key informant interviews. Involved in the research were human and animal health experts, and woreda (Woreda is a third level of administrative unit in Ethiopia following region and zone) level government officials. Thematic framework analysis was used to analyse the data. Zoonotic diseases are a significant public health concern and have a substantial economic burden on local livelihoods. Poor access to human and livestock health services contributed towards the widespread transmission of zoonotic pathogens. In most cases, pastoralists were aware of the possibility of zoonotic disease transmission from livestock to humans and were cognizant of infections contracted from animals. However, the level of risk perception from zoonotic diseases and the subsequent measures of protection was poor. In almost all cases, despite pastoralists’ awareness of zoonotic diseases, they did not consider zoonoses as harmful to human health as they are to animals. It was evident that the burden of zoonotic diseases was high in livestock camps away from settlements in Hamer while for Dassenetch the resettlement clusters created a conducive environment for transmission. This research underscored the importance of engaging with local communities on the risk implications of zoonotic diseases including those related to their food habits and practices.